The first records of Bartheletia paradoxa (Bartheletiomycetes, Agaricomycotina) in Ukraine - Hayova, V.P.; Tykhonenko, Yu.Ya. (Український ботанічний журнал, 2017)
A new for Ukraine basidiomycete fungus, Bartheletia paradoxa, strictly confined to leaves of Ginkgo biloba, is reported. The species was collected on fallen leaves of G. biloba in November 2016 and 2017 in three localities within Kyiv city. Both conidial and telial stages were found. Morphological descriptions of conidial sori, conidia, secondary conidia, telia and teliospores are provided. More data on phenology of the fungus is added. Information about distribution of B. paradoxa is considered. To date, the species is known from several countries in Europe as well as from Korea and Japan in East Asia. Described from outside of the ancient distribution area of the host plant, B. paradoxa has not yet been reported within the presumptive native range of Ginkgo in China. Moreover, despite wide cultivation of G. biloba globally, this quite conspicuous fungus has not yet been recorded in some mycologically rather well studied regions, like North America or New Zealand. The article is illustrated by original micrographs.